Risk factors for acute kidney injury among patients with chikungunya: a multi-center experience from the 2017 chikungunya outbreak in Dhaka, Bangladesh (BIRDEM Medical Journal, 2019)
Background: Chikungunya is an emerging viral infection in Bangladesh. This self-limiting febrile illness may have acute life-threating features including cardiomyopathy and encephalitis. Acute kidney injury (AKI) is less well described complication of chikungunya. This study was designed to evaluate risk factors for AKI among patients with chikungunya virus infection.Methods: This case-control study was done in 3 different centers in Dhaka, Bangladesh from July to October 2017. Adult patients (>18 years) with confirmed diagnosis of chikungunya were included in this study. AKI was diagnosed as per Kidney Disease: Improving Global Outcomes (KDIGO) Clinical Practice Guideline for Acute Kidney Injury. Patients suffering from chikungunya complicated by AKI were cases and those without AKI were controls.Results: Total patients were 107 (male 61) with a mean age of 35.6 (range 19-84) years. Common comorbidities were diabetes mellitus (DM) (20.6%), hypertension (17.8%) and chronic kidney disease (CKD) (12.1%). Common presentations included fever (86.9%) or recent history of fever (13.1%), joint pain (88.8%), rash (23.4%), pruritus (15.9%), gastro-intestinal (GI) features like diarrhea and/or vomiting (28%), lymphadenopathy (12.1%), gum swelling/oral ulcer (4.1%) and oedema (8.4%). Fourteen (13.1%) patients required hospitalization. Eleven (10.3%) cases were complicated by AKI. Among the risk factors for AKI, comorbidities like DM (OR 28.73, 95% CI 5.57-148.10, p 0.0001) and CKD (OR 31.0, 95% CI 2.94-326.7, p